An approach to detect smartphone addiction through activity recognition and app usage behaviour - Uz Zaman, Nur; Akther, Afroza; Tabassum, Nowshin; Samrat, Md. Khaliduzzaman Khan; Khan, Swad Mustasin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.